Outcomes of Minimally Invasive Oblique Lumbar Interbody Fusion in Patients with Lumbar Degenerative Disease with Rheumatoid Arthritis - Akbary, Kutbuddin; Quillo-Olvera, Javier; Lin, Guang-Xun; Jo, Hyun-Jin; Kim, Jin-Sung (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Purpose of Study Standard treatment protocols for lumbar degenerative lesions in the setting of rheumatoid arthritis (RA) are lacking. The purpose of this study was to evaluate the clinical and radiologic outcomes of minimally invasive oblique lumbar interbody fusion (MI-OLIF) in RA patients having degenerative lumbar spine lesions.Methods This was a retrospective hospital-based case series (evidence level 4). Eight patients with degenerative lumbar disease with significant back pain and neurologic claudication underwent MI-OLIFwith polyetheretherketone cage insertion and posterior pedicle screw instrumentation. The clinical outcomes were measured by the numerical rating scale (NRS) for back and leg pain and the Oswestry Disability Index (ODI), and radiologic outcomes were studied on radiographs, computed tomography, and magnetic resonance imaging. Minimum follow-up duration was 1 year.Results Mean NRS results for back and leg pain preoperatively were 6.3 and 7.1 that improved to 2.6 and 2 for back and leg pain, respectively, at last follow-up. The mean ODI scores preoperatively were 58.02 that improved to 39.06 at last follow-up. All patients had good functional outcomes, good fusion rates, and were able to continue their activities of daily living without much disability at last follow-up.Conclusion MI-OLIF in patients with symptomatic lumbar spine degenerative lesions with RA seems to provide good short-term clinical and radiologic outcomes.
Keywords: oblique lumbar interbody fusion; rheumatoid arthritis; degenerative lumbar spine disease; MI-OLIF